Education for Sustainable Consumption: A Social Reconstructivism Model - McGregor, Sue (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
Social reconstructivism is suggested as an appropriate curriculum philosophy for education for sustainable consumption (ESC). Couched in framing the consumer culture as a powerful social institution that needs to be challenged and reformed, the position paper begins by defining sustainable consumption, including symptoms of unsustainable consumption and barriers to consuming sustainably. This is followed by a description of the social reconstructivist curriculum philosophy and model. Related contributions include ESC values, principles, and issues, the notion of catalytic education, and a description of instructional strategies recommended to help put social reconstructivism-informed ESC curricula into motion. The intent is to create a generation of learners who see themselves as social change agents by assuming that ownership of learning leads to ownership of actions. Keywords: education for sustainable consumption, social reconstructivism, catalytic education, consumer culture, social institutions